2015
DOI: 10.1039/c5cp04061b
|View full text |Cite|
|
Sign up to set email alerts
|

Is there an intramolecular hydrogen bond in 2-halophenols? A theoretical and spectroscopic investigation

Abstract: The Abraham solute hydrogen bond acidity parameter A can be derived both from physical methods, A(Gen) and NMR experiments, A(NMR) and results for a large number of hydroxylic solutes show that the two methods agreed very well. However for halophenols the values of A(NMR) were not consistent with the A(Gen) values. The values of A(NMR) suggest that there is no intra-molecular hydrogen bonding in any of the 2-halophenols. In contrast the values of A(Gen) indicate that there is no intra-molecular hydrogen bondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 33 publications
5
36
0
Order By: Relevance
“…The ability of X-HÁ Á ÁF-C interactions to create five-membered rings seems more questionable. For example, theoretical calculations, and IR and NMR measurements in nonpolar solvents suggest that there is no intramolecular hydrogen bond in 2-fluorophenol (Abraham et al, 2015). This is consistent with earlier work by Cormanich et al (2012).…”
Section: Introductionsupporting
confidence: 87%
“…The ability of X-HÁ Á ÁF-C interactions to create five-membered rings seems more questionable. For example, theoretical calculations, and IR and NMR measurements in nonpolar solvents suggest that there is no intramolecular hydrogen bond in 2-fluorophenol (Abraham et al, 2015). This is consistent with earlier work by Cormanich et al (2012).…”
Section: Introductionsupporting
confidence: 87%
“…The QM energy calculated for a ternary complex of 2-chlorophenol, NMA, and W1 in their crystal structure conformations showed a <0.1 kcal/mol difference in E MP2 between the i - and o- rotamers, which would account for the near equal distribution among the rotamers ( Figure 9 ). Furthermore, Abraham et al 68 showed that 2-halophenols adopt a trans -OH in water but a cis -OH with a weak intramolecular HB between the hydroxyl and halogen in organic solvents. The pocket where m X Y18 sits is partially solvent exposed, resulting in the hydroxyl having only a slight preference as an HB donor to the Cl over W1.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, unlike the incorporation of strong electron‐withdrawing groups at the 2‐positions of 37 (nitro) and 40 (methyl ester) the 2‐chloro‐ and 2‐bromophenol adducts afforded 2‐chlorophenyl‐ 54 and 2‐bromophenyl‐ 55 in 68 and 71 % yields, respectively. Explaining the relatively weak “ ortho ‐halo effect” it is known they form only moderately strong intramolecular X⋅⋅⋅HO bonds (X=Cl or Br) . Incorporating substrates equipped with more than one halogen was explored using the trifluoromethyl group.…”
Section: Resultsmentioning
confidence: 99%